Identification and morphology of a rhyacophilid caddisfly larva from Cyprus: Rhyacophila aphrodite Malicky 1975 - Waringer, Johann; Malicky, Hans (Zootaxa, 2019)
Rhyacophila aphrodite Malicky 1975 is a micro-endemic species of Cyprus and the only rhyacophilid caddisfly recorded on this island. This paper describes the previously unknown larva of this species. Information on the morphology of the final larval instar is given, and the most important diagnostic features are illustrated. In the context of existing Rhyacophilidae identification keys, the larva of R. aphrodite belongs to the group fitted with one single-filament gill on each side of the meso- and metathoraces and one four-filament gill on each side of abdominal segments I to VIII. In addition, a sword process is present on each anal proleg. The distal anal claw tooth is perpendicular to the longitudinal axis of the anal claw and shorter than half of the anal claw width at the distal tooth insertion.